2015
DOI: 10.3389/fncom.2015.00026
|View full text |Cite
|
Sign up to set email alerts
|

Phase-dependent modulation as a novel approach for therapeutic brain stimulation

Abstract: Closed-loop paradigms provide us with the opportunity to optimize stimulation protocols for perturbation of pathological oscillatory activity in brain-related disorders. In this vein, spiking activity of motor cortex neurons and beta activity of local field potentials in the subthalamic nucleus have both been used independently of each other as neuronal signals to trigger deep brain stimulation for alleviating Parkinsonism. These approaches were superior to the standard continuous high-frequency stimulation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…to an initial state of (3) in \gamma , then the isochron associated with \bfita (0) is the set of all initial conditions \bfitb (0) for which (4) lim t\rightar\infty | | \bfita (t) -\bfitb (t)| | = 0, where | | \cdot | | can be any norm. Using this definition, the isochron of an initial condition gives a sense of its asymptotic convergence to the periodic orbit.…”
Section: Background: Isochrons and Isostables Of Coupled Theta Model mentioning
confidence: 99%
“…to an initial state of (3) in \gamma , then the isochron associated with \bfita (0) is the set of all initial conditions \bfitb (0) for which (4) lim t\rightar\infty | | \bfita (t) -\bfitb (t)| | = 0, where | | \cdot | | can be any norm. Using this definition, the isochron of an initial condition gives a sense of its asymptotic convergence to the periodic orbit.…”
Section: Background: Isochrons and Isostables Of Coupled Theta Model mentioning
confidence: 99%
“…For other approaches, it could be possible to utilise the lower amplitude information. Several authors have postulated that phase-dependent stimulation could be an effective therapeutic strategy for treating motor symptoms (Rosin B et al 2011;Azodi-Avval R and A Gharabaghi 2015;Holt AB et al 2016;Meidahl AC et al 2017) and we have recently demonstrated the potential efficacy of this approach (Holt AB et al 2018). Together, these studies show that it may be possible to utilise phase-dependent stimulation at low amplitudes, disrupting the most synchronised population of neurons before pathologically sustained beta bursts arise.…”
Section: Temporal Dynamics Of Neuronal Synchronisation In the Stnmentioning
confidence: 79%
“…Increased clinical benefit is suggested by targeting specific pathological neurophysiological phases in PD . Also, phase‐dependent aDBS might induce long‐lasting beneficial effects attributed to possible long‐term potentiation/depotentiation in the STN . Moreover, phase‐dependent aDBS reduced tremor severity and prevented breakthrough tremor while consuming less energy compared to cDBS .…”
Section: Stimulation Parameter Modulation In Adbsmentioning
confidence: 99%
“…6,32,34 Also, phase-dependent aDBS might induce long-lasting beneficial effects attributed to possible long-term potentiation/depotentiation in the STN. 81 Moreover, phase-dependent aDBS reduced tremor severity and prevented breakthrough tremor while consuming less energy compared to cDBS. 82 Studies assessing these suggested advantages of phase dependency in aDBS are required.…”
Section: Amplitude Modulation Approachesmentioning
confidence: 99%